DEMOKRASI ATAU ISLAMOPHOBIA di NEGARA HUKUM: ANALISIS KEBIJAKAN PEMERINTAH TERHADAP ISLAM DI INDONESIA - Suprima Suprima (Program Studi Hukum Keluarga Islam, 2023)
This research was conducted on the emergence of several controversial government policies and have the possibility of leading to Islamophobia. The purpose of this study is to analyze several controversial policies that are seen from two aspects, namely from the perspective of democracy and Islamophobia. The method used is a literature study by analyzing policies based on a review of related theories. The results of this study are that the policies made by the government, namely the minister of religion, have the possibility of Islamophobia. These controversial policies when viewed from two different perspectives have the potential for greater Islamophobia because they create a bad perception of Islam. In addition, these policies are not based on appropriate democracy, but tend to lead to the personal decisions of policy makers.